Oral changes in pregnant and nonpregnant women: A case-control study - Santosh R Patil (Journal of Orofacial Sciences, 2013)
Aim: The numerous changes occurring during pregnancy affect every body system, resulting in localized physical alterations in almost all parts of the body, including the oral cavity. The aim of the present study was to find the incidence of oral conditions seen particularly in the pregnant women than in the nonpregnant women. Materials and Methods: The oral health condition of 120 pregnant women referred to the outpatient department of Jodhpur Dental College General Hospital from a gynecology clinic were examined and compared with 120 nonpregnant women. The pregnant women were divided in a 3 groups of 40 each, according to the stage of pregnancy. The common oral conditions seen during pregnancy were assessed. Results: Pregnant women had a higher incidence of gingivitis and pyogenic granuloma. Gingivitis and erosion of teeth due to vomiting was seen commonly in the 3 rd trimester. The results indicated that pregnancy had an effect on the oral condition, which was mainly due to the hormonal changes seen during this period rather than other factors. Conclusion: Women planning a pregnancy or those already pregnant should be informed about the role of oral health during pregnancy and the possible outcomes of these conditions for the welfare of their foetus. They should be referred to the dental clinician for necessary counselling for preventive oral self-care and treatment, if required.